An Aerial View of a Black Man Suffering From the Menace of Crude Oil (The Black Gold) Soot (Global Journal of Management and Business Research, 2020)
Petroleum oil is the black gold of the continent regarded as black Africa which has numerous mineral resources which have been of tremendous benefit to the black continent and it has since the last three decades, played a critical role in the Nigerian economy. On the average, it has accounted for not less than 70% of the Federal government revenue, haven given 90% of the nation's foreign exchange earnings, and with a 12% real gross domestic product (GPD). Oil is one of the sources of energy in Nigeria, particularly and the world in general. The economic and political fortune of our great nation Nigeria is being shaped by Petroleum Oil which plays the dominant role in Nigeria after the end of the Nigeria-Biafran civil war of 1967 to 1970.
Keywords: petroleum oil; crude oil; soot; niger delta region; GDP; environmental degradation; economic poverty; nigerian economy